2013
DOI: 10.1186/1479-5868-10-58
|View full text |Cite
|
Sign up to set email alerts
|

Associations between eating meals, watching TV while eating meals and weight status among children, ages 10–12 years in eight European countries: the ENERGY cross-sectional study

Abstract: BackgroundTo assess the association of eating meals, and never watching TV while eating meals, with weight status among children, ages 10–12 years across Europe.Methods7915 children (mean age: 11.5 years) in eight European countries (Belgium, Greece, Hungary, the Netherlands, Norway, Slovenia, Spain and Switzerland) completed a questionnaire at school. Data on meals eaten the day before questionnaire administration and the frequency of eating meals while watching TV were collected. Height and weight of the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
75
4
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 45 publications
(62 reference statements)
13
75
4
7
Order By: Relevance
“…This was in contrast to the findings from a recent study that included eight European countries which found that the odds of being overweight was lower for children who reported to never watch TV at lunch and dinner compared to those who did (Vik et al, 2013). On the other hand, the prevalence of overweight and obesity in this study showed a significant independent association with eating during emotional stresses.…”
Section: Discussioncontrasting
confidence: 99%
“…This was in contrast to the findings from a recent study that included eight European countries which found that the odds of being overweight was lower for children who reported to never watch TV at lunch and dinner compared to those who did (Vik et al, 2013). On the other hand, the prevalence of overweight and obesity in this study showed a significant independent association with eating during emotional stresses.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the time spent on TV viewing was not directly assessed, but a positive association was found between preschool overweight/obesity and eating while watching TV. Several studies have shown that eating in front of the TV is positively associated with higher BMI among children, an association that is independent of the overall time spent watching TV or the sedentary behavior that accompanies it [60,61]. Dubois et al showed that four- to five-year-old children who frequently ate in front of the TV had higher BMI relative to their peers, while no significant associations were found between the child’s BMI and the overall time spent watching TV [3].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Some home factors shown to be important determinants of the dietary and physical activity habits of children include parental modeling of healthful eating, [9][10][11][12][13][14] regularity of meals, [15][16][17] and parental participation in regular physical activity. 12,18 While a large number of studies have been conducted on the role of child eating behaviours and parental feeding practices on obesity risk in children [19][20][21] and a few studies have been conducted on the role of mothers' and fathers' own eating behaviours, 22,23 to our knowledge, no studies have simultaneously assessed the role of child, mother and father eating behaviours -something that is necessary to understand the relative impacts of these behaviours. To address this gap in knowledge and further inform the development of family-based interventions designed to reduce the risk of childhood overweight and obesity, the objectives of this study were to identify key eating behaviours among peri-adolescent children and their parents and to estimate the associations between these behaviours and five measures of body composition in children, including body mass index, waist-to-height ratio, waist-to-hip ratio, waist girth, and hip girth.…”
mentioning
confidence: 99%